The Silences of Labour Music History : Music as a Tool for Social Change - Rantanen, Saijaleena (Intellect, 2025)
The article discusses the reasons why certain people and phenomena have long been excluded from the writing of music history in the field of Finnish musicology. At the same time, it considers the significance that conscious or unconscious exclusion can have on our perceptions of the past. The perspective is the research of working-class music in the context of Finnish immigrants in North America at the turn of the 20th century. The key methodological concepts are awareness-raising research, the ethical turn in historical research, and marginal history, which make it possible to bring to light historical figures and events that for one reason or another have remained invisible. The article also describes a collaboration between a researcher and musicians that brought a hundred years of workers' songs back to life.
Keywords: musiikinhistoria; työväenlaulut; työväenliike